Carbon Nanowires: Peapod‐like Li3VO4/N‐Doped Carbon Nanowires with Pseudocapacitive Properties as Advanced Materials for High‐Energy Lithium‐Ion Capacitors (Adv. Mater. 27/2017). Issue 27 (July 2017) - Shen, Laifa; Lv, Haifeng; Chen, Shuangqiang; Kopold, Peter; van Aken, Peter A.; Wu, Xiaojun; Maier, Joachim; Yu, Yan
Abstract : In article number1700142, Xiaojun Wu, Yan Yu, and co‐workers report a highenergy lithium‐ion capacitor using Li3 VO4 /N‐doped carbon nanowires as the anode and activated carbon as the cathode. The N‐doped carbon‐encapsulated Li3 VO4 nanowires display a low insertion voltage and fast rate kinetics, features that are better than are found for many other Li + insertion anodes. The combination of the Li3 VO4 anode and the activated carbon cathode could lead to promising lithium‐ion capacitors that are not attainable by conventional electrochemical energy‐storage systems.